Bond Characteristics and Financial Performance Among Top 100 Listed Companies in Malaysia - Nurul Suhada Sufian; Aliana Shazma Amir; Siti Nor Junita Mohd Radzi (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2022)
This study examines the relationship between bond characteristics and financial performance by top 100 Malaysian public listed companies. The study uses 100 firm-year observations drawn from the population of non-financial companies in 2021. To achieve the objectives of this study, quantitative method of analysis is employed. Using multiple regression analysis, the results reveal that bond issuance and bond ratings have a positive significant impact on financial performance. The findings imply that the fact that the advantage of keeping bonds over stocks for investors is that bonds have a positive rate of return with fixed income. The performance of bonds further surpasses risk adjustment levels. Besides, the higher rated bond or known as investment grade bond the safer and stable investment by the bondholders which may enhance financial performance. The present study is unique as it helps the researcher and others to explore the practice and prospect of bond market in Malaysia. Exploring the practice of bonds in Malaysia, it will help to readers to understand the importance of invest in bond as it can lower the risk of the company’s portfolio.